Mathematical Modelling of Malaria Disease Transmission and Control. - Muhangi, Benard (Kabale University, 2024)
This study focused on mathematical modelling of malaria disease transmission and control. Besides, by using the comparison theorem and the theory of uniform persistence, the study will respectively, assess the global stability of the nontrivial disease-free equilibrium and the existence of positive periodic control measures. This study suggested and analyzed the transmission dynamics of malaria disease in a population using a nonlinear mathematical model. The deterministic compartmental model was examined using stability theory of differential equations. The reproduction number was obtained to be asymptotically stable conditions for the disease-free, and the endemic equilibria were determined. Moreso, the qualitatively evaluated model incorporates time-dependent variable controls which was aimed at reducing the proliferation of malaria disease. The possible influence of exploring a single control, the combination of two, and the three controls on the spread of the disease was also investigated.